Application of the Prudential Principle in Giving Banking Kredit - Dewi, Elsa Dianita Puspita (Journal of Law, Politic and Humanities, 2025)
Banking institutions is institution Which collect And channel fund in public. banking very role And have share in effort enhancement level life public Indonesia through development economy public. Bank own program distribution fund For public Which Wrong the only one often called with credit . Credit provided to banks to be distributed to customers contains risks. So that in its implementation, every credit grant to customers must be careful and careful in observing the principle of prudence. Method research used that is juridical normative with use legislative approach and conceptual approach. Type material the law used are primary, secondary And tertiary. From the results study can concluded the first is that in providing banking credit, the bank must always apply the principle of prudence in order to minimize the risk of the bank's operational business with the aim of ensuring that the bank is always in a healthy, liquid and solvent condition. The principles used must be in accordance with existing regulations so that they will not cause defects in the world of credit. Losses resulting from credit can worsen the image of a bank. Besides That Wrong One impact is credit become congested And For do solution credit congested there is a number of strategy with method scheduling return , requirements return And arrangement return . Second , Violation principle caution in credit banking give rise to consequence law . Where to the party doing it violation will given penalty law form sanctions criminal nor regulated fines in Law No. 10 of 1998 concerning Banking . Banking crimes occur or fall into the realm of "state loss", abuse of authority resulting in corruption crimes